PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS INKUIRI PADA POKOK BAHASAN MEMBUAT HIDANGAN PENUTUP UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMK - Romadhoni, Ita Fatkhur; Nurlaela, Luthfiyah; Nur, Mohamad (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2013)
ABSTRACT This study aims to improve student learning outcomes through the implementation learning package of inquiry based learning for topic dessert in second semester of class XI at Vocational High School of Tegallalang, Gianyar, Bali. The study was conducted in two stages, namely the level of preparation that aims to develop tools pursue the 4-D model from Thiagarajan, et al., (1974), followed by the implementation of classroom learning. Data obtained as a result of the following assessment: learning tool qualification approval ratings with highly qualified category to apply to students (94.3%). Achievement learning with the implementation of inquiry learning model (90.3%) in both categories. Mastery of student learning outcomes included formulating the problem, formulating hypotheses, identifying variables and operational definitions of variables, conduct experiments and draw conclusions can be said to improve learning outcomes of students (35%) on the pretest to (85%) at the end of the field trials. The response of students to the aspects: (1) An interest component (86%) with the category very interested, (2) currency of the component (79%) with a fairly new category, and (3) ease in understanding the components (35%) with the category is not easy. Constraints in learning activities especially students not accustomed to the process skills, so there need more time to practice skills. Based on the analysis of data, it can be concluded that the development of a model of learning by using the material inquiry make dessert can improve student learning outcomes in Vocational High School. Keywords: Inquiry Learning Model, Dessert, Learning Outcomes